Sikap Syukur sebagai Proses Pembentukan Budi Pekerti pada Remaja (Studi Deskriptif terhadap Siswa Kelas 10 di SMK Pasundan 4 Bandung) - Winda Widyaningsih; Iu Rusliana; Naan Naan (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This research aims to discuss what gratitude is and an attitude of gratitude in 10th grade students of SMK Pasundan 4 Bandung in the city of Bandung. The second is to find out what manner and behavior are for the 10th grade students of SMK Pasundan 4 Bandung in the city of Bandung. Third, to find out the role of gratitude in shaping character in adolescents. This study uses a qualitative research model and the source of the data used comes from the results of observations, interviews and various literatures related to the research theme. The results of this study indicate that character is a person's awareness of behaving according to the rules or norms that apply in society and gratitude is the acknowledgment of a servant to God for the blessings that have been given to him accompanied by the servant's submission to God. Most of the students of SMK Pasundan 4 Bandung in the city of Bandung who were the research subjects had a high level of gratitude as evidenced by the fulfillment of all the indicators of gratitude found in Sufism, also proving that almost all of the students who were the research subjects had noble manner and the last which shows a positive continuity between the attitude of gratitude in adolescents to the process of forming adolescent manners.